SUBJECT HEADINGS AUTHORITY LIST (SHAL): A COMPUTERIZATION PROJECT AT CDA LIBRARY (SUBJECT HEADINGS AUTHORITY LIST (SHAL) / UN PROJET D’AUTOMISATION POUR LA BIBLIOTHEQUE DU MINISTERE D L’AGRICULTURE - Islam, M. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
see pdf